2013
DOI: 10.1007/s10529-013-1199-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of Wnt1 and Fzd1 in the spinal cord pathogenesis of amyotrophic lateral sclerosis-transgenic mice

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease characterized by chronic progressive degeneration of motor neurons resulting in muscular atrophy, paralysis, and ultimately death. We have investigated the expression of Wnt1 and Fzd1 in the spinal cords of SOD1G93A ALS transgenic mice, SOD1G93A-transfected N2a cells, and primary cultured astrocytes from SOD1G93A transgenic mice. In addition, we provided further insight into the role of Wnt1 and Fzd1 in the pathogenesis of ALS transgenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 15 publications
1
35
0
1
Order By: Relevance
“…Several studies have shown that this pathway is upregulated in motor neurons of ASL model mice [32][33][34][35]. In the spinal cord of SOD1(G93A) ALS transgenic mice, expression of Wnt2, Wnt7a and GSK-3beta has been determined [32].…”
Section: Als and Wnt/beta-catenin Pathwaymentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have shown that this pathway is upregulated in motor neurons of ASL model mice [32][33][34][35]. In the spinal cord of SOD1(G93A) ALS transgenic mice, expression of Wnt2, Wnt7a and GSK-3beta has been determined [32].…”
Section: Als and Wnt/beta-catenin Pathwaymentioning
confidence: 99%
“…Changes in Wnt5a and Fzd2 expression in the spinal cord of SOD1(G93A) transgenic mice (ALS), SOD1(G93A) transfected NSC-34 cells and primary cultures of astrocytes from SOD1(G93A) transgenic mice have been observed [35]. Expression of Wnt1 and Fzd1 has been found to be increased in the spinal cords of SOD1G93A ALS transgenic mice [34]. In the in vitro model of ALS (G93A mutated forms of human Cu/Zn superoxide dismutase-1; SOD1), a cytosolic aggregation of beta-catenin has been observed.…”
Section: Als and Wnt/beta-catenin Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…A growing body of evidence suggests that Wnt signaling may be involved in homeostasis and disease progression in adult tissues, [17][18][19][20][21][22][23][24][25][26] including the spinal cord.…”
mentioning
confidence: 99%